2013
DOI: 10.1182/blood-2012-12-471698
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenetics shows that not all MBL are equal: the larger the clone, the more similar to CLL

Abstract: Key Points• Low-count and high-count monoclonal B-cell lymphocytosis (MBL) have distinct immunogenetic signatures, with only the latter resembling CLL.• Rather than a true premalignant condition, low-count MBL may merely reflect immune senescence or result from persistent antigen stimulation.Chronic lymphocytic leukemia (CLL) -like monoclonal B-cell lymphocytosis (MBL) shares common immunophenotype and cytogenetic abnormalities with CLL, from which it is discriminated by a cutoff value of 5 3 10 9 /L circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 52 publications
7
60
0
4
Order By: Relevance
“…This might occur in an antigen-independent way as early as at the HSC level, as recently proposed by Kikushige et al (2011). Therefore, these early expansions would more likely translate into an oligoclonal MBL lo stable condition, in which clonality will not directly translate into malignancy (Henriques et al, 2013;Vardi et al, 2013); further clonal B-cell expansion might depend on additional micro-environmental factors (e.g. infections) (Casabonne et al, 2012) and/or acquisition of specific (additional) genetic changes by the expanded B-cells (Henriques et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This might occur in an antigen-independent way as early as at the HSC level, as recently proposed by Kikushige et al (2011). Therefore, these early expansions would more likely translate into an oligoclonal MBL lo stable condition, in which clonality will not directly translate into malignancy (Henriques et al, 2013;Vardi et al, 2013); further clonal B-cell expansion might depend on additional micro-environmental factors (e.g. infections) (Casabonne et al, 2012) and/or acquisition of specific (additional) genetic changes by the expanded B-cells (Henriques et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
“…Biassed usage of specific IGHV genes in both CLL and MBL (Henriques et al, 2013;Vardi et al, 2013) would further support the existence of selective pressurese.g. inherited genetic predisposition factors and/or still unidentified pathogen(s) -that may favour the expansion of specific IGHV-IGHD-IGHJ clones, not only at the B-lymphocyte stage but potentially also at the haematopoeitic stem cell (HSC) compartment (Alizadeh & Majeti, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…LC-MBL increases with age, being present in 75% of individuals older than 90 years of age, seems to remain stable over time, and exhibits an immunogenetic signature that is distinct from CLL, more similar to the IG gene usage within the elderly. Together with the paucity of CLL-specific BcR IG stereotypy in LC-MBL, this justifies the interpretation of LC-MBL as a manifestation of immune senescence leading to immune restriction likely due to chronic antigenic stimulation (46). Therefore, one might speculate that the "CLL-type" cytogenetic abnormalities of LC-MBL may be acquired during lymphocyte development and maturation, perhaps in conjunction with a particular type of antigenic triggering, and associate Here, however, we propose a possible continuum of events that transit this progenitor cell through distinct clonal conditions and may eventually lead to true malignant transformation.…”
Section: Origin Of Cll and The Mbl Conundrummentioning
confidence: 88%
“…6 MBL was subclassified into a CD5 1ve, CD23 1ve CLL-like category; a CD5 1ve, CD23 2ve, CD20 bright atypical CLL category; and a CD5 2ve category. 3,4 Many subsequent studies have confirmed the biological similarities between clinical CLL-like MBL and early stage CLL 7 and the low rate of progression to CLL requiring therapy. 8,9 Although the diagnostic criteria for CLL-like clinical MBL have been used to refine the diagnosis of CLL, the cutoff of 5 3 10 9 /L 3,4 clonal B lymphocytes for distinguishing clinical MBL from CLL is arbitrary, lacking clinical and/or biological justification.…”
Section: Introductionmentioning
confidence: 96%